Application of a neurofuzzy mathematical model in the development of a local oven design (2009)
This paper presents a contribution on the development of a neurofuzzy mathematical model that aids in capturing and analyzing the various parameters in oven design. The oven was designed specifically for domestic and commercial baking operations. The neurofuzzy methodology was used to regulate the oven baking temperatures to acceptable standards. Particular use was made of neurofuzzy model since it is an improvement on the process design. The work was motivated by the need for a more reliable and easily understandable methodology that guides decision makers in making correct decisions in a timely manner. The results obtained demonstrated that it is feasible to apply the model in practice.